2013
DOI: 10.1002/eat.22231
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia nervosa patient diagnosed with previously unsuspected ADHD in adulthood: Clinical case report, literature review, and diagnostic challenges

Abstract: There is increasing literature suggesting a link between attention-deficit hyperactivity disorder (ADHD) and eating disorders (EDs), especially bulimia nervosa. ADHD is under-diagnosed in girls and children of high intelligence are typically missed. We identified a case of a 23-year-old woman suffering from severe bulimia nervosa and previously unsuspected ADHD in adulthood; we diagnosed and treated her with extended-release methylphenidate. We performed a literature review on the ADHD and bulimia nervosa como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…These 6 cases are consistent with findings of psychostimulant use in binge eating disorder patients and bulimia nervosa patients with comorbid ADD/ADHD . In particular, the results provide additional evidence that safety can be maintained in a carefully selected and monitored bulimia nervosa population that is being treated with psychostimulants.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These 6 cases are consistent with findings of psychostimulant use in binge eating disorder patients and bulimia nervosa patients with comorbid ADD/ADHD . In particular, the results provide additional evidence that safety can be maintained in a carefully selected and monitored bulimia nervosa population that is being treated with psychostimulants.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, case reports of this comorbid population (bulimia nervosa and ADHD) have noted incidental improvements in binge/purge behaviors after psychostimulants were initiated for ADHD. A review of the 17 available cases revealed that when treated with a psychostimulant, 10 patients demonstrated full remission of bulimia nervosa symptoms, 6 patients demonstrated improvement, and only 1 patient relapsed after weight loss and subsequent noncompliance . In bulimia nervosa patients without ADHD, there have only been 2 cases described, both of which noted decreases in binge/purge behaviors after the initiation of psychostimulants …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulants commonly used to treat ADHD strengthens the attention capacity, thus facilitating active participation in the treatment process. Additionally, stimulants used to treat ADHD are reported to dramatically reduce concomitant BN symptoms in a number of case reports (Drimmer, ; Dukarm, ; Ersson, Klanger, Wallsten, Nilsson, & Lindstrom, ; Guerdjikova & McElroy, ; Ioannidis, Serfontein, & Muller, ; Keshen & Ivanova, ; Schweickert, Strober, & Moskowitz, ). Likewise, stimulants are shown to reduce ED symptoms in BN without established ADHD in a number of case reports (Keshen & Helson, ; Messner, ; Sokol, Gray, Goldstein, & Kaye, ) and in a small randomized controlled trial (Ong, Checkley, & Russell, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings, however, have been limited to case studies (Ioannidis et al, 2014;Keshen and Ivanova, 2013) or small clinical populations (McElroy et al, 2007). One reason for the effectiveness of these medications is that ADHD is comorbid with BN and BED.…”
Section: Introductionmentioning
confidence: 99%